2017
DOI: 10.1128/cvi.00273-17
|View full text |Cite
|
Sign up to set email alerts
|

A Single Intramuscular Dose of a Plant-Made Virus-Like Particle Vaccine Elicits a Balanced Humoral and Cellular Response and Protects Young and Aged Mice from Influenza H1N1 Virus Challenge despite a Modest/Absent Humoral Response

Abstract: Virus-like-particle (VLP) influenza vaccines can be given intramuscularly (i.m.) or intranasally (i.n.) and may have advantages over split-virion formulations in the elderly. We tested a plant-made VLP vaccine candidate bearing the viral hemagglutinin (HA) delivered either i.m. or i.n. in young and aged mice. Young adult (5-to 8-week-old) and aged (16-to 20-month-old) female BALB/c mice received a single 3-g dose based on the HA (A/California/07/2009 H1N1) content of a plant-made H1-VLP (i.m. or i.n.) split-vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 41 publications
(44 reference statements)
3
27
0
Order By: Relevance
“…In all of these trials however, subjects with serious comorbid conditions were excluded. These clinical observations are consistent with previous studies showing that healthy BALB/c mice up to 16–20 months of age can be protected from lethal challenge with a single dose of the plant-derived VLP vaccine despite relatively weak (younger animals) or absent (older animals) antibody responses [22]. In the current work, we extended our mouse model to the limit of the murine life-span.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In all of these trials however, subjects with serious comorbid conditions were excluded. These clinical observations are consistent with previous studies showing that healthy BALB/c mice up to 16–20 months of age can be protected from lethal challenge with a single dose of the plant-derived VLP vaccine despite relatively weak (younger animals) or absent (older animals) antibody responses [22]. In the current work, we extended our mouse model to the limit of the murine life-span.…”
Section: Discussionsupporting
confidence: 88%
“…The development of vaccines that can stimulate cellular responses in addition to antibodies may be of particular interest for this population since older individuals appear to derive significant benefit from cellular memory [3, 21]. We have recently demonstrated that VLP vaccines made in plants that carry HA trimers of either seasonal or pandemic influenza viruses can protect animals (mice, ferrets) in lethal challenge studies despite low and, in some cases, even completely absent antibody responses [22, 23]. After footpad injection in a mouse vaccination model, these VLPs have been shown to move to regional lymph nodes (LN) within minutes where they preferentially associate with antigen-presenting cells (APC) and B cells [24] linked with a rapid increase in LN cellularity and dendritic cell activation [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,12,13 These vaccines have been shown to elicit strong and cross-reactive antibody responses against both seasonal and pandemic influenza strains in animal models and human trials. 1416 They also induce polyfunctional and cross-reactive HA-specific CD4 + T cell responses. 14,15,17 Simultaneous administration of a plant-derived H1-VLP vaccine with ovalbumin (OVA) was recently shown to elicit an OVA-specific CD8 + T cell response in C57BL/6 mice.…”
Section: Introductionmentioning
confidence: 99%
“…cell line, which has been proved to be a safe, high-yield, and low-cost vaccine production method (Bright et al, 2008). It has been shown that VLPs, as new vaccine candidates, can be produced with a high yield in a short time period and are also promising platforms to enhance the (Hodgins et al, 2017;Price, Lo, Misplon, & Epstein, 2018;Ren et al, 2018;Trondsen et al, 2015), although other ways, such as the intradermal route, are under investigation . A critical requirement for comparing these routes usually includes a magnitude of stimulated inflammatory as well as protective immune responses.…”
Section: T Cell and Dendritic Cell Responsesmentioning
confidence: 99%